Effects of population, family, and diet on craniofacial morphology of Icelandic Arctic charr (Salvelinus alpinus). (7th January 2013) - Küttner, Eva; Parsons, Kevin J.; Robinson, Beren W.; Skúlason, Skúli; Danzmann, Roy G.; Ferguson, Moira M.
<x xml:space="preserve">Abstract</x> We evaluated hypotheses of intralacustrine diversification and plastic responses to two diet environments in Icelandic Arctic charr (Salvelinus alpinus). Full‐sib families of progeny of wild polymorphic charr from two lakes where morphs vary in their degree of phenotypic and ecological divergence were split, with half of the offspring reared on a benthic and half on a limnetic type of diet to estimate family norms of reaction. We focused on variation in craniofacial traits because they are probably functionally related to diet and complement a previous study of body shape in these charr. A hierarchical analysis of phenotypic variation between lakes, pairs of morphs within each lake, and two families within each morph found that phenotypic variation partitioned between families relative to morphs was reduced in the more ecologically diversified population, which is consistent with adaptive diversification. The effect size of plastic responses between lake populations was similar, suggesting little difference in the degree of canalization in contrast to a previous analysis of body form plasticity. Thus, the role that plastic morphological responses play in the adaptive diversification of morphs and different lake populations of Arctic charr may depend on the trait. © 2013 The Linnean Society of London